Pengaruh Penetapan Harga Jual Sembako Terhadap Minat Beli Konsumen dengan Customer Behavior sebagai Intervening Sesuai Perspektif Islam di Sumatera Utara - Mhd. Agung Pratama Trg; Tri Inda Fadhila Rahma; Aqwa Naser Daulay (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
In conventional markets, pricing is in accordance with the demand and supply curves of the goods/services. The balance of demand and sales, willingness between the parties to the transaction, justice, honesty, trustworthiness are some of the points that are considered in pricing according to the Islamic perspective. Islam provides freedom in pricing, which means that all forms of price concepts that occur in buying and selling transactions are allowed in Islamic teachings as long as there is no argument that prohibits it. However, it should also be noted how the application of prices according to the Islamic perspective can have an influence on buying interest and customer behavior. This study aims to determine the effect of setting the selling price of goods / services on buying interest and customer behavior (as intervening) according to an Islamic perspective.Â  The population in this study was taken from the total population of Medan City per the 2020 population census. The data analysis technique in this study uses the Structural Equation Modeling (SEM) method. The results showed, in the intervening influence test, showed a p value of 0.000 <0.05. This means that price on purchase intention has a significant influence through customer behavior as intervening. Then, seen in the table, the value of the loading factor value> 0.70, which means that the data results are valid.